The Whisper of the Follicle: A Systematic Review of Micro Ribonucleic Acids as Predictors of Oocyte Quality and In Vitro Fertilization Outcomes - Charalampos Voros; Antonia Varthaliti; Diamantis Athanasiou; Despoina Mavrogianni; Anthi-Maria Papahliou; Kyriakos Bananis; Aristotelis-Marios Koulakmanidis; Antonia Athanasiou; Aikaterini Athanasiou; Constantinos G. Zografos; Athanasios Gkirgkinoudis; Maria Anastasia Daskalaki; et al. (Cells)
Background: MicroRNAs (miRNAs) in follicular fluid (FF) are being recognized as important regulators of ovarian function and biomarkers of reproductive success. This systematic analysis investigates FF-derived miRNAs and their relationship to polycystic ovarian syndrome (PCOS) and in vitro fertilization (IVF) outcomes. Methods: Following PRISMA recommendations, 21 original papers were included that looked at miRNA expression in FF or granulosa cells from women undergoing IVF, with or without PCOS. The study design, miRNA profiling methodologies, IVF protocols, and clinical results were gathered and analyzed. Results: Across the investigations, 15 miRNAs were regularly implicated, including miR-132, miR-320, miR-222, miR-224, miR-146a, and miR-93. Downregulation of miR-132 and miR-320 was consistently detected in PCOS and associated with decreased steroidogenesis. Elevated miR-222 and miR-146a were linked to insulin resistance and follicular inflammation. In IVF, miR-202-5p and miR-224 were elevated in high-quality embryos and successful cycles, indicating that they have roles in granulosa cell proliferation and estrogen synthesis. MiRNA dysregulation was linked to critical pathways, such as PI3K/AKT, NF-κB, TGF-β, and WNT. Conclusions: Specific FF miRNAs are consistently linked to PCOS pathogenesis and IVF effectiveness. Their use into noninvasive biomarker panels could improve embryonic selection and personalized reproductive care.